2016
DOI: 10.24095/hpcdp.36.8.02
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours associated with indoor tanning based on the 2012/13 Manitoba Youth Health Survey

Abstract: Introduction Although indoor tanning causes cancer, it remains relatively common among adolescents. Little is known about indoor tanning prevalence and habits in Canada, and even less about associated behaviours. This study explores the prevalence of adolescent indoor tanning in Manitoba and its association with other demographic characteristics and health behaviours. Methods We conducted secondary analyses of the 2012/13 Manitoba Youth Health Survey data collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Forest plot for past‐year exposure in adults and college students. Table S1 Studies included in the meta‐analysis …”
mentioning
confidence: 99%
“…Forest plot for past‐year exposure in adults and college students. Table S1 Studies included in the meta‐analysis …”
mentioning
confidence: 99%
“…It is possible that UV indoor tanning is controlled by a number of different factors and that pigmentation is not comparatively as relevant as other determinants. For instance, it has been reported that indoor tanning is associated with mental health problems 54 , physical activity and dietary practices 55 , and other risky behaviours 56, 57 . Moreover, a recent GWAS meta-analysis on sun-seeking behaviour 58 , adjusted for tanning ability and SEP, identified 5 loci related to behavioural traits, including addiction.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that UV indoor tanning is controlled by a number of different factors and that pigmentation is not comparatively as relevant as other determinants. For instance, it has been reported that indoor tanning is associated with mental health problems [53], physical activity and dietary practices [54], and other risky behaviours [55,56]. Moreover, a recent GWAS meta-analysis on sun-seeking behaviour [57], adjusted for tanning ability and SEP, identified five loci related to behavioural traits, including addiction.…”
Section: Discussionmentioning
confidence: 99%